Concrete Quality Design F'C 21 MPa Using SNI 7656:2012 Method Using Local Materials (C Ibu Selatan Quarry) - Etwar Luang; Joni Hermanto; Muhammad Usamah (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
The rapid development of infrastructure in various sectors, including buildings, bridges, and towers, has increased the demand for concrete as a primary construction material. Concrete is widely used due to its advantages such as high compressive strength, durability, fire resistance, and economic efficiency. The compressive strength of concrete is generally evaluated at 28 days, while early-age strength development can be used to estimate its final performance.This study aims to evaluate the characteristics of local Class C quarry materials in Ibu Selatan District and to design a concrete mix with a target compressive strength of F’c 21 MPa using the SNI 7656:2012 method. Fine and coarse aggregates were obtained from local quarry sources in West Halmahera Regency. The engineering properties of the materials were tested to ensure compliance with concrete requirements.Concrete specimens were cast in cylindrical molds measuring 15 cm × 30 cm and tested for compressive strength at curing ages of 3, 7, 14, 21, and 28 days. The results show that the compressive strength increased with curing age, indicating normal strength development. The 28-day compressive strength reached the target design value of F’c 21 MPa, confirming that the mix design method is effective for producing normal concrete using local materials.The study concludes that local quarry materials from Ibu Selatan District are suitable for use in structural concrete and can reduce dependence on imported materials while remaining economically efficient.